The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.4142/jvs.2017.18.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis in diabetes mellitus

Abstract: Diabetes mellitus (DM) is becoming a lifestyle-related pandemic disease. Diabetic patients frequently develop electrolyte disorders, especially diabetic ketoacidosis or nonketotic hyperglycemic hyperosmolar syndrome. Such patients show characteristic potassium, magnesium, phosphate, and calcium depletion. In this review, we discuss a homeostatic mechanism that links calcium and DM. We also provide a synthesis of the evidence in favor or against this linking mechanism by presenting recent clinical indications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 64 publications
0
40
1
1
Order By: Relevance
“…Regarding the effect of the HG condition on calcium signaling, previous studies have suggested an altered calcium homeostasis in diabetics animals (Ahn, Kang, & Jeung, ; Pereira et al, ; Sorrentino et al, ). In cardiomyocytes, a deregulation of Ca 2+ cycling and diminished Ca 2+ influx have been shown under diabetic conditions (Bergh, Hjalmarson, Sjögren, & Jacobsson, ; Lu et al, ; Pereira et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the effect of the HG condition on calcium signaling, previous studies have suggested an altered calcium homeostasis in diabetics animals (Ahn, Kang, & Jeung, ; Pereira et al, ; Sorrentino et al, ). In cardiomyocytes, a deregulation of Ca 2+ cycling and diminished Ca 2+ influx have been shown under diabetic conditions (Bergh, Hjalmarson, Sjögren, & Jacobsson, ; Lu et al, ; Pereira et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, insulin release is a process dependent on calcium, and as low vitamin D levels can lead to hypocalcaemia, this can also disrupt insulin secretion . Vitamin D regulates extracellular calcium to ensure normal calcium influx, thereby enhancing insulin action and signal transduction .…”
Section: Vitamin D and Type 2 Diabetesmentioning
confidence: 99%
“…Associations between IHP and T2DM are not well understood as IHP is a rare disease, with a period prevalence of 7.2 per million population in Japan 10. Although previous in vitro and in vivo studies have reported on the importance of extracellular calcium concentrations for insulin secretion,11–15 the insulin secretion levels following glucagon stimulation tests did not increase after the treatment of hypocalcaemia in this case (table 3); this suggested that the diabetes was not secondary to hypocalcaemia. The low PTH levels may have weakened insulin secretion in this case, as in vitro studies have shown that PTH (1–34) directly stimulates insulin release from pancreatic islets through the stimulation of cyclic adenosine monophosphate (cAMP) production or activation of protein kinase C 16 17.…”
Section: Discussionmentioning
confidence: 58%